Viral Interference Between Dengue Virus and Hepatitis C Virus Infections. (3rd July 2020) - Liang, Po-Cheng; Chen, Kuan-Yu; Huang, Chung-Hao; Chang, Ko; Lu, Po-Liang; Yeh, Ming-Lun; Huang, Chung-Feng; Huang, Ching-I; Hsieh, Meng-Hsuan; Dai, Chia-Yen; Lin, Zu-Yau; Chen, Shinn-Chern; et al.
Abstract: Both dengue virus (DENV) and hepatitis C virus (HCV) belong to the Flaviviridae family and could induce hepatitis. We aimed to investigate the interference between them. In total, 515 patients confirmed with dengue fever (DF) were enrolled. Thirty-two patients (6.21%) were seropositive for anti-HCV; 12 of 32 anti-HCV-positive patients had detectable HCV-RNA at presentation of DF. The proportion of dengue hemorrhagic fever was comparable between patients with or without anti-HCV and between those with or without HCV-RNA. Eleven of 32 patients received HCV-RNA testing during a median interval of 23 months after DF, which revealed significantly increased HCV-RNA levels (5.43 ± 0.77 vs 3.09 ± 1.24 log IU/mL, follow-up vs acute-DF phase; P = .003). Four of 11 patients with baseline HCV-RNA values before DF demonstrated a nadir viremia during acute DF. We also included age-, sex-, and follow-up duration–matched HCV-monoinfected patients as controls; higher delta HCV-RNA changes were demonstrated in patients with DF than in controls during the follow-up period (2.34 ± 1.15 vs –0.27 ± 0.76 log IU/mL; P < .001). Further in vitro experiments showed that HCV nonstructural protein 5A was downregulated in Con1 HCV replicon cells infected by DENV1. These clinical and experimental findings suggested possible viral interference in DENV/HCV. However, HCV viremia did not affect the disease outcomes of DF.